Media Convergence in Indonesian Radio: Integrating Terrestrial and Multiplatform Broadcasting - Harliantara, Harliantara; Sjuchro, Dian Wardiana; Rutambuka, Theogene (Jurnal Kajian Jurnalisme, 2026)
Background: Digital disruption has changed the global broadcasting landscape, shifting radio from a rigid terrestrial medium to a more fluid multiplatform ecosystem. Although digital platforms dominate the attention economy, radio in Indonesia has shown unique resilience by combining legacy trust with digital network-based interaction. Purpose: This study aims to reformulate radio content distribution strategies and explain how radio management adapts to the logic of platformisation in the digital age. Methods: This research used a multi-site qualitative approach with case studies on three types of radio stations in Indonesia. Data was collected through in-depth interviews and reinforced with digital ethnography. Results: The results show that radio's sustainability is supported by three main pillars. First, algorithmic grooming, which is a radio strategy to tailor content to the logic of visual platform algorithms. Second, distributional decoupling, where radio identity no longer depends entirely on physical frequencies. Third, the utilization of radio as a ‘human infrastructure’ that builds emotional closeness and parasocial interaction with the audience. This study also found the important role of radio in regional areas as a backup information medium when digital networks are disrupted. Conclusion: This study concludes that the revival of radio has occurred through its transformation from a frequency provider to a flexible and adaptive ‘everywhere media’ entity. Implications: Theoretically, this study contributes to the development of media convergence theory by emphasizing that strategic fluidity, the ability to operate across digital and terrestrial boundaries, is key to radio's resilience in the digital age.